The use of medicinal plants species by the Temuan tribe of National Botanical Garden Shah Alam, Malaysia - Khamis, Shamsul; Go, Rusea; Abdul Manap, Tajuddin (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
Results on the use of medicinal plants in the forest reserve at National Botanical Garden Shah Alam, Malaysia are presented. Although this forest is surrounded by activities of rapid sosio-economic development, is still serves as a resource for indigenous people to find alternative medicinal plant for treating diseases beside readily modern medicine. A total of 66 plant species were recognized with 15 uses recorded. The collection includes herbaceous plants, trees, shrubs, lianas and epiphytes. They were grouped into 12 methods of application namely as a drink, food, drop, cooking material, shampoo, bath, rub, massage, poultice, bandage, smoke and boil. Some plants can be multipurpose, used to treat more than one disease, and the plant part most frequently used is root.